2013
DOI: 10.4103/0019-5545.120557
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity and marital satisfaction among spouses of men with alcohol dependence

Abstract: Background:Alcohol dependence has adverse health and social consequences; Alcohol related problems primarily occur within the family context and maximum impact is felt on spouses, given the intimate nature of their relationship. Spouses play an important role in treatment programs related to alcohol. There is thus a need to study psychiatric morbidity and marital satisfaction in spouses of alcohol dependent patients in order to understand and address such issues.Aims:The aim of this study was to assess the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 25 publications
5
45
2
Order By: Relevance
“…4 Kishor et al from Karnataka, India reported higher prevalence of alcohol dependence (70%) in cases who were unskilled labours. 6 Most of the alcohol dependence cases in present study were from lower middle socioeconomic status (44.92%) followed by lower class (27.53%). Various studies across India have reported a similar result of higher dependence in cases belonging to lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…4 Kishor et al from Karnataka, India reported higher prevalence of alcohol dependence (70%) in cases who were unskilled labours. 6 Most of the alcohol dependence cases in present study were from lower middle socioeconomic status (44.92%) followed by lower class (27.53%). Various studies across India have reported a similar result of higher dependence in cases belonging to lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 50%
“…Kishor et al from Karnataka, India reported that a mean duration of alcohol dependence among the cases was 4 years (±3.4) which is almost similar to present study while Tyagi et al from Rajasthan, India found the mean duration to be 9.60±2.79 years which is higher than present results. 6,7 On applying SADD we observed that majority of the cases had severe level of alcohol dependence (47.82%) followed by moderate level of dependence (44.92%). Almost similar results were reported by Kishor et al in their study.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations